College students' writing self-efficacy and writing self-regulated learning strategies in learning English as a foreign language. (June 2020) - Sun, Ting; Wang, Chuang
Abstract: This study aims to examine how writing self-efficacy and writing self-regulated learning (SRL) strategies are related to writing proficiency among college students in an English as a foreign language (EFL) context. The Questionnaire of English Writing Self-Efficacy (QEWSE) and the Questionnaire of English Writing Self-Regulated Learning Strategies (QEWSRLS) were administered to 319 sophomore Chinese students. Their writing proficiency was measured by their writing scores on the writing section of the College English Test Band 4 (CET-4). The results showed that EFL students reported a moderate level of self-efficacy and infrequent use of SRL strategies in the course of writing. Moreover, both writing self-efficacy and writing SRL strategies contributed significantly to the prediction of students' writing proficiency. Since self-efficacy and self-regulation are crucial to students' writing proficiency, the current study provides classroom teachers with insights about how to incorporate instructions into EFL classrooms to improve students' writing outcomes.